(untitled) (International Journal of Engineering and Computer Science, 2024)
As the global population ages, the demand for long-term care (LTC) services has risen significantly. Long-term care facilities that support residents with chronic illnesses, disabilities, or age-related conditions face numerous challenges in delivering effective and efficient care. Traditional methods of monitoring residents’ health often rely on periodic check-ups, which may overlook subtle changes in health, contributing to delayed interventions and escalating healthcare costs. AI-enabled remote health monitoring represents a transformative solution to these challenges. By leveraging artificial intelligence (AI) technologies, such as wearable devices, smart sensors, and predictive analytics, healthcare providers can continuously monitor vital signs, detect health issues early, and personalize care plans for each resident. This white paper explores the current landscape of AI-driven monitoring in LTC, its benefits, challenges, and future potential.